2021
DOI: 10.1007/s40121-021-00525-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bamlanivimab/Etesevimab and Casirivimab/Imdevimab in Preventing Progression to Severe COVID-19 and Role of Variants of Concern

Abstract: Introduction The aim of this study was to evaluate the risk of hospitalization or death in patients infected by SARS-CoV2 variants of concern (VOCs) receiving combinations of monoclonal antibodies (mAbs), bamlanivimab/etesevimab or casirivimab/imdevimab. Methods Observational prospective study conducted in two Italian hospitals (University Hospital of Pisa and San Donato Hospital, Arezzo) including consecutive outpatients with COVID-19 who received bamlanivimab/etesevim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 16 publications
4
68
0
Order By: Relevance
“…Notably, the U.S. federal government reinstated circulation of bamlanivimab-etesevimab on August 27, 2021 in areas where variant resistance to this mAb is < 5%, based on in vitro data of activity against the Delta variant, and lack of activity against the Beta, Gamma, Delta plus, and B.1.621 variants. 31,32 The similar effectiveness of bamlanivimab-etesevimab and casirivimab-imdevimab in the current trial supports this decision. Also aligning with these data is a recent observational study of 165 patients that found no difference in hospitalization or death between bamlanivimab-etesevimab and casirivimab-imdevimab in patients infected with Alpha, but worse outcomes with bamlanivimab-etesevimab in patients infected with Gamma.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Notably, the U.S. federal government reinstated circulation of bamlanivimab-etesevimab on August 27, 2021 in areas where variant resistance to this mAb is < 5%, based on in vitro data of activity against the Delta variant, and lack of activity against the Beta, Gamma, Delta plus, and B.1.621 variants. 31,32 The similar effectiveness of bamlanivimab-etesevimab and casirivimab-imdevimab in the current trial supports this decision. Also aligning with these data is a recent observational study of 165 patients that found no difference in hospitalization or death between bamlanivimab-etesevimab and casirivimab-imdevimab in patients infected with Alpha, but worse outcomes with bamlanivimab-etesevimab in patients infected with Gamma.…”
Section: Discussionsupporting
confidence: 64%
“…26 A recent observational study reached a different conclusion and found similar effectiveness between bamlanivimab and casirivimab-imdevimab. 31 However, this study analyzed patients treated between November 2020 and February 2021, prior to widespread emergence of variants and U.S. federal decisions to halt bamlanivimab distribution.…”
Section: Discussionmentioning
confidence: 99%
“…B.1.1.7, B.1.351, P.1, B.1.617.2, and B.1.1.529 VOCs (recently renamed by WHO as Alpha, Beta, Gamma, Delta and Omicron, respectively) first identified in the United Kingdom, South Africa, Brazil, India, and Botswana, carry different mutations among which D614G change became dominant early in the pandemic [ 18 ]. VOCs may increase virus transmissibility, disease severity, reduce neutralization by antibodies generated during previous infection or vaccination, and reduce the effectiveness of treatments or vaccines, or diagnostic detection failures [ 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, monoclonal antibodies (mAbs) developed from CP, directed against specific target of SGP and selected on the basis of antiviral potency and target affinity showed efficacy in reducing the risk of disease progression and death. Currently approved mAbs have not the same activity against VoC [21] . Ongoing clinical trials are evaluating the safety and efficacy of second-generation mAbs with activity against circulating VoC and more easily administered by IM route.…”
Section: Perspectivesmentioning
confidence: 96%
“…The efficacy of CP is likely to depend on the ‘match’ between the strain-specific transfused anti-SARS-CoV-2 antibodies in donor plasma and the infecting virus variant in the recipient. The SARS-CoV-2 variant (B.1.1.7) detected in England in December 2020, spread rapidly to become the dominant SARS-CoV-2 variant in most European countries, including Italy [21] . Whilst B.1.1.7 has changes in the spike glycoprotein that could theoretically modify antigenicity, only modest reductions in neutralization by CP have been reported.…”
Section: Cp With Antibodies Active Against Dominant Variant Of Concernmentioning
confidence: 99%